Differential Regulation of Human Serotonin Receptor Type 3A by Chanoclavine and Ergonovine - Sanung Eom; Woog Jung; Jaeeun Lee; Hye Duck Yeom; Shinhui Lee; Chaelin Kim; Heui-Dong Park; Junho H. Lee (Molecules, 2021)
Irritable bowel syndrome (IBS) is a chronic disease that causes abdominal pain and an imbalance of defecation patterns due to gastrointestinal dysfunction. The cause of IBS remains unclear, but intestinal-brain axis problems and neurotransmitters have been suggested as factors. In this study, chanoclavine, which has a ring structure similar to 5-hydroxytryptamine (5-HT), showed an interaction with the 5-HT3A receptor to regulate IBS. Although its derivatives are known to be involved in neurotransmitter receptors, the molecular physiological mechanism of the interaction between chanoclavine and the 5-HT3A receptor is unknown. Electrophysiological experiments were conducted using a two-electrode voltage-clamp analysis to observe the inhibitory effects of chanoclavine on Xenopus oocytes in which the h5-HT3A receptor was expressed. The co-application of chanoclavine and 5-HT resulted in concentration-dependent, reversible, voltage-independent, and competitive inhibition. The 5-HT3A response induced by 5-HT was blocked by chanoclavine with half-maximal inhibitory response concentration (IC50) values of 107.2 µM. Docking studies suggested that chanoclavine was positioned close F130 and N138 in the 5-HT3A receptor-binding site. The double mutation of F130A and N138A significantly attenuated the interaction of chanoclavine compared to a single mutation or the wild type. These data suggest that F130 and N138 are important sites for ligand binding and activity. Chanoclavine and ergonovine have different effects. Asparagine, the 130th amino acid sequence of the 5-HT3A receptor, and phenylalanine, the 138th, are important in the role of binding chanoclavine, but ergonovine has no interaction with any amino acid sequence of the 5-HT3A receptor. The results of the electrophysiological studies and of in silico simulation showed that chanoclavine has the potential to inhibit the hypergastric stimulation of the gut by inhibiting the stimulation of signal transduction through 5-HT3A receptor stimulation. These findings suggest chanoclavine as a potential antiemetic agent for excessive gut stimulation and offer insight into the mechanisms of 5-HT3A receptor inhibition.